(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to improve the learning outcomes of Grade VI students in the subject of Islamic Religious Education and Character Building through the implementation of a Game-Based Learning model supported by Flashcard Memory Game media, specifically regarding the topic of qada and qadar (divine decree and predestination) at SDN No. 277 Sambirejo, Luwu Regency. The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles; each cycle comprised the stages of planning, action implementation, observation, and reflection. The results indicate an improvement in learning outcomes following the implementation of the intervention. During the pre-cycle stage, the student mastery rate was 40% with an average score of 66. Following the intervention, mastery increased to 72% with an average score of 80 in Cycle I, and reached 96% with an average score of 92 in Cycle II. This improvement demonstrates that the application of the Game-Based Learning model supported by Flashcard Memory Game media can enhance student learning outcomes regarding the topic of qada and qadar within the context of this study. Thus, the implemented model and media offer an alternative instructional approach that is more interactive and enjoyable, thereby supporting the improvement of student learning outcomes.